2004
DOI: 10.1596/1813-9450-3366
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Development: A Cross-Section Approach

Abstract: This paper assesses the effects of knowledge on economic growth. By using an array of indicators, each of which represents an aspect of knowledge, as independent variables in cross-section regressions that span 92 countries for the period 1960 to 2000, the paper shows that knowledge is a significant determinant of long-term economic growth. In particular, we find that the stock of human capital, the level of domestic innovation and technological adaptation, and the level of information and communications techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 50 publications
2
48
0
14
Order By: Relevance
“…This innovation, according to him can be attained by allocating to young entrepreneurs an important role particularly because of their ability to innovate. Chen and Dahlman (2004), point out that the stock of human capital, associated with appropriate knowledge acquired through relevant education and the level of domestic innovation and technological adaptation, are those that lead a country to development. Specifically: "A well-educated and skilled population is ISSN 2162-3058 2016 essential to the efficient creation, acquisition, dissemination and utilization of relevant knowledge, which tends to increase total factor productivity and hence economic growth" 1 .…”
Section: Human Development Is About Equal Life Chances For All It Inmentioning
confidence: 99%
“…This innovation, according to him can be attained by allocating to young entrepreneurs an important role particularly because of their ability to innovate. Chen and Dahlman (2004), point out that the stock of human capital, associated with appropriate knowledge acquired through relevant education and the level of domestic innovation and technological adaptation, are those that lead a country to development. Specifically: "A well-educated and skilled population is ISSN 2162-3058 2016 essential to the efficient creation, acquisition, dissemination and utilization of relevant knowledge, which tends to increase total factor productivity and hence economic growth" 1 .…”
Section: Human Development Is About Equal Life Chances For All It Inmentioning
confidence: 99%
“…It was a core component of a project exploring the New Economy sponsored by the European Commission in 2001-2003 [6] and served the EC again in 2009 for a project examining the impact of information and communications technology (ICT) and on sustainability [7]. Forecasts from IFs supported the National Intelligence Council's Project 2020: Mapping the Global Future [8] and Global Trends 2025: A Transformed World [9].…”
Section: The International Futures (Ifs) Modelmentioning
confidence: 99%
“…Barro [6] reported that one extra year of male upper-level education raised growth by 1.2% per year.  Chen and Dahlman [7] concluded that a rise of 20% in average years of schooling raises annual growth by 0.15 percent and that an increase in average years by 1 year raises growth by 0.11 percent.  Jamison, Lau, and Wang [8] used the Barro-Lee measure of average years of school for males between 15 and 60, but concluded that the "effect was small".…”
mentioning
confidence: 99%
“…A leading representative of the new growth theory, P. M. Romer, argues that the economic future of nations is a function of their capacity to innovate, which in turn depends on the level of education and research available at universities (Romer 1990). Based on extensive research conducted in 92 countries during the period 1960-2000, D. H. C. Chen and C. J. Dahlmanshowed that an increase of one percent in the number of patents granted by the USPTO 1 increases the rate of economic growth by 0,19 percentage points (Chen, 2004).W. Baumol points out that 'almost all the economic growth which has occurred since the eighteenth century, in the final analysis is due to innovation.'…”
Section: Introductionmentioning
confidence: 99%